Environmental Conditions and Sincerity affects Cortisol and ?-Endorphins Plasma Levels in Young Healthy Subjects Undergoing Dawood’s Fast - Indri Ngesti Rahayu; Bambang Purwanto; Moh. Ali Azis; M. Yogiarto; Aryati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Prevention of Coronary Heart Disease by identifying risk factors facilitates the planning ofprevention interventions. The prevalence of non-communicable disease (NCD) increases with one of therisk factors for NCD being an unbalanced diet. Dawood’s fasting is one of the sunnah fastings that can bedone at any time except at times that are forbidden to fast. This fast is a combination model of TRF and ADF(modified ADF = MADF).Objective: To prove that MADF for six consecutive weeks can increase levels of the hormone ?-endorphinsand reduce levels of the hormone cortisol in peripheral blood circulation.Materials and Methods: Quasi-experimental research with a comparative design of a non-equivalentcontrol group with a population of PP students. Hidayatullah Surabaya with the purposive sampling methoduntil the number of samples required was met as many as 34 people and divided into two groups, namelycontrol and MADF treatment for six consecutive weeks. Sampling was carried out at the pre-test, at the endof the third week for the middle and at the post-test. All subjects in both groups received the same nutritiontwice a day for 42 days. The subject gets spiritual motivation from competent resource persons to givespiritual spark twice.Result: Dawood’s fasting (MADF) for six consecutive weeks did not cause significant differences comparedto control on cortisol and ?-endorphins (p> 0.05). However, Dawood’s fasting (MADF) for six consecutiveweeks decreased the mean values of cortisol levels due to the effect of fasting, although there was also asignificant difference in the control group. Meanwhile the ?-endorphins mean values was increased at themiddle of study, and then decreased at the end of the study, with a significant difference in the both groupbefore and after treatment.Conclusion: There was no difference in cortisol and ?-endorphins levels in healthy young adult subjectsundergoing Dawood’s fast due to the influence of the same environmental conditions and a change in thesincerity of the subjects.